2019
DOI: 10.1111/jiec.12920
|View full text |Cite
|
Sign up to set email alerts
|

Toward a dynamic evaluation of mineral criticality: Introducing the framework of criticality systems

Abstract: A new methodology to quantify minerals’ criticalities is proposed—the criticality systems of minerals. In this methodology, four types of agents—mineral suppliers, consumers, regulators of the market, and others, such as the communities near mining operations—interact with each other through three types of indicators: constraints, such as the political stability in the mining regions, the mineral's substitutability and economic importance; agents’ interactions, such as buyer–seller bargaining; and interactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Even in that case, the multi-level aspect is represented as an interplay between international and global levels (excluding the regional level) and the flow aspect mainly covers only primary metal resources circuits, not the recycled metals circuit. We can cite the work of the team of Knoeri and Riddle [30,31] or that of the team of Yuan [32] as rare examples of these works. The date of the latter work (between 2013 and 2021) and the state-of-the-art regarding the BTP sector confirms that the application of the ACE on mineral resources is still at its early stages.…”
Section: Methodology Proposalmentioning
confidence: 99%
“…Even in that case, the multi-level aspect is represented as an interplay between international and global levels (excluding the regional level) and the flow aspect mainly covers only primary metal resources circuits, not the recycled metals circuit. We can cite the work of the team of Knoeri and Riddle [30,31] or that of the team of Yuan [32] as rare examples of these works. The date of the latter work (between 2013 and 2021) and the state-of-the-art regarding the BTP sector confirms that the application of the ACE on mineral resources is still at its early stages.…”
Section: Methodology Proposalmentioning
confidence: 99%
“…MFA enriches the thinking on criticality by identifying the nodes in the chain that are out of balance from a technical, environmental, or geopolitical point of view. On the environmental impacts of a sector's activity, a commonly adopted approach is life-cycle analysis, LCA, to make choices, for example for how to process substances, based on these impacts, as has been done in the gold [10] and platinum [11] sectors. As for the time factor, Graedel's team [2] admits that no unique approach exists to assess it.…”
Section: International Journal Of Environmental Sciences and Natural Rementioning
confidence: 99%
“…One of the main disadvantages attributed to ACE is often their low acceptance in the mining field [22], unlike the MFA and LCA approaches, which are more widely known and used by experts. However, in the past seven years, there is growing interest in the implementation of ACE for criticality: [23] on lithium, [24] on minerals in general, [3] on rare earths, and [11] on platinum. These few ACE projects have allowed us to begin to grasp some of the limitations pointed out by the state of art.…”
Section: International Journal Of Environmental Sciences and Natural Rementioning
confidence: 99%
See 1 more Smart Citation
“…The United States National Research Council has stated an element criticality as "the risk that supplies of the element might not be routinely available together with an assessment of the impact of such a restriction on the evaluating organization" (Nassar et al, 2012); nevertheless, a national level criticality assessment requires a robust status-quo analysis with multiple indicators to address both economic threats and environmental implications (Kolotzek et al, 2018). We cautiously examined a number of criticality studies published (British Geological Survey, 2015;Calvo et al, 2018;Ciacci et al, 2016;Daw, 2017;Dewulf et al, 2016;European Commission, 2010;European Commission, 2017;Fang et al, 2018;Glöser-Chahoud et al, 2016;Graedel et al, 2012;Hatayama and Tahara, 2015;Nassar et al, 2012;Öko-Institut, 2009;Rosenau-Tornow et al, 2009;United States National Research Council, 2008;Yuan et al, 2019;Zepf et al, 2014); however, some drawback could be observed in adopting these methods for each metal at the national level. Particularly, certain indicators presented in some methodologies are a challenge to determine since data acquisition obstacles (Schrijvers et al, 2020).…”
mentioning
confidence: 99%